EMOTIONAL BURNOUT SYNDROME: EFFECT ON CLINICAL INERTIA AND MEDICAL PRACTICE STEREOTYPES - R. A. Khokhlov; E. V. Minakov; G. I. Furmenko; N. M. Akhmedzhanov (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To estimate the prevalence of burnout in primary care physicians and its influence on medical practice stereotypes and on clinical inertia.Material and Methods. The anonymous single-stage poll was carried out among 184 primary care physicians. The questionnaire included information about sex, age, period and conditions of work, established stereotypes of practices. Burnout was evaluated by Russian analog of Maslach Burnout Inventory. It was defined in high level of emotional exhaustion and depersonalization and low level of personal accomplishment 11 questions were developed to reveal of suboptimal medical practice (for example, “I do not discuss treatment options with patient and do not give full answers to his questions” or “I make diagnostic and treatment errors despite of my professional knowledge and inexperience”).Results. The burnout syndrome (or extreme grade of emotional burnout) occurs in 13,1% and high level of emotional burnout – in 49,7% of primary care physicians. Features of suboptimal medical practice are usually found in 24,2% of primary care physicians at least monthly. It expresses more often in improper attitude to paqtients and their problems associated with a disease. Thus, burnout contributes to improper attitude to patients. Professional burnout affects established work stereotypes and can promote development of physician’s clinical inertia.Conclusion. As the burnout is common among primary care physicians, an adequate monitoring and prevention of this state is necessary in medical labour management.